2006
DOI: 10.1113/jphysiol.2006.117374
|View full text |Cite
|
Sign up to set email alerts
|

Transporters involved in regulation of intracellular pH in primary cultured rat brain endothelial cells

Abstract: Fluid secretion across the blood-brain barrier, critical for maintaining the correct fluid balance in the brain, entails net secretion of HCO 3 − , which is brought about by the combined activities of ion transporters situated in brain microvessels. These same transporters will concomitantly influence intracellular pH (pH i ). To analyse the transporters that may be involved in the maintenance of pH i and hence secretion of HCO 3 − , we have loaded primary cultured endothelial cells derived from rat brain micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
91
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(105 citation statements)
references
References 76 publications
10
91
3
Order By: Relevance
“…Several mechanisms are responsible for keeping the pH i of the endothelial cells forming the BBB more acidic than the surrounding medium under basal condition (Taylor et al, 2006). In vitro experiments have shown that a change in the extracellular medium can lead first to an abrupt, sustained change in pH i .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several mechanisms are responsible for keeping the pH i of the endothelial cells forming the BBB more acidic than the surrounding medium under basal condition (Taylor et al, 2006). In vitro experiments have shown that a change in the extracellular medium can lead first to an abrupt, sustained change in pH i .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments have shown that a change in the extracellular medium can lead first to an abrupt, sustained change in pH i . Later-acting cell mechanisms then attempt to restore the basal pH i as illustrated by in vitro BBB experiments (Hsu et al, 1996;Nicola et al, 2008;Taylor et al, 2006). We therefore adapted the in situ brain perfusion procedures to perform acute pH i changes at the mouse BBB, as these alterations were more predictable, and take place on the same time scale as the brain perfusion time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations